Increased Subcortical Sodium Levels in Patients with Progressive Supranuclear Palsy - Prasuhn, Jannik; Göttlich, Martin; Grosser, Sinja S.; Reuther, Katharina; Ebeling, Britt; Bodemann, Christina; Hanssen, Henrike; Nagel, Armin Michael; Brüggemann, Norbert (Biomedicines, 2022)
Progressive supranuclear palsy (PSP) is a debilitating neurodegenerative disease characterized by an aggressive disease course. Total and intracellular-weighted sodium imaging (Na-23-MRI) is a promising method for investigating neurodegeneration in vivo. We enrolled 10 patients with PSP and 20 age- and gender-matched healthy control subjects; all study subjects underwent a neurological examination, whole-brain structural, and (total and intracellular-weighted) Na-23-MRI. Voxel-wise analyses revealed increased brainstem total sodium content in PSP that correlated with disease severity. The ROI-wise analysis highlighted additional sodium level changes in other regions implicated in the pathophysiology of PSP. Na-23-MRI yields substantial benefits for the diagnostic workup of patients with PSP and adds complementary information on the underlying neurodegenerative tissue changes in PSP.
CRIS-Team WoS Importer:2022-08-12